BERMAIN PERAN DALAM MENGEMBANGKAN KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN DI TK KHADIJAH 77 KEMBIRITAN KECAMATAN GENTENG KABUPATEN BANYUWANGI - Ria Octa Viana; Atmaul Hukma; Fitriatul Masruroh; Eka Ramiati (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The development of interpersonal intelligence is a process of learning in children about cooperation, empathy and establishing contact with friends. So the process of children's growth and development must always be considered so that it runs optimally, at Khadijah 77 Kembiritan Kindergarten has implemented role-playing activities in developing children's interpersonal intelligence at the age of 5-6 years. This study aims to describe the implementation of role-playing activities in developing interpersonal intelligence of children aged 5-6 years at Khadijah 77 Kindergarten, and describe the development of interpersonal intelligence of 5-6 year old children at Khadijah 77 Kembiritan Kindergarten. This research uses a descriptive qualitative approach with the type of field research, the subjects of this research are the Principal, Class Teachers and 15 students aged 5-6 years at Khadijah 77 Kindergarten. The data collection process uses several methods, namely Observation, Interviews and Documentation. Based on the results of this study, the Based on the results of this study, it shows that the implementation of role-playing activities is carried out in 3 stages, namely: the first is planning which includes determining themes, learning tools, and learning media. Then the second implementation: Managing the position of the children (dividing the group), explaining and exemplifying how to play the role and the third evaluation, in Khadijah Kindergarten the evaluation is carried out twice in each semester one and two. This study shows the results that the development of interpersonal intelligence in children aged 5-6 years through role-playing activities runs optimally, this can be seen from the achievement indicators sourced from the Child Development Achievement Level Standards (STPPA): 1) Children are able to cooperate, 2) children are able to empathize with others, 3) children are able to make friends or make contacts, 4) the child is able to organize a group of people towards a common goal, 5) the child is able to understand the feelings of others